Protective Eyewear for Pesticide Applicators - Brett Bultemeier (EDIS)
Protective eyewear is one of the most essential pieces of PPE an applicator can utilize when it is required. This new 3-page publication of the UF/IFAS Pesticide Information Office discusses the types of protective eyewear and how best to select and maintain these particular pieces of PPE. Written by Brett Bultemeier. https://edis.ifas.ufl.edu/pi287